Design Automation and Testing of MEDA-Based Digital Microfluidic Biochips: A Brief Survey. Issue 5 (2nd September 2020) - Howladar, Pampa; Roy, Pranab; Rahaman, Hafizur
ABSTRACT: In recent years, application of digital microfluidic biochips (DMFBs) in an extended range, suffers from a few limitations namely (a) flexibility on droplet size (b) requirement of special fabrication process (c) need for integrated sensor systems for real-time detection. To overcome these challenging issues, a DMFB based new advanced microelectrode dot array architecture (MEDA) with advanced characteristics such as field programmability, higher reconfigurability and scalability has been introduced. This paper provides a comprehensive survey of MEDA-based DMFBs, a review on fluidic level synthesis as well as chip-level design to solve problems such as malfunctioning microelectrodes, droplet classification, system automation, biomedical detection and surface flatness testing, followed by a brief description on fault Modeling, testing and error recovery technique on MEDA architecture. Finally, the survey concludes with suggestions for future advancement possibilities in the areas of development of MEDA-based Biochips.